Relationship between the spontaneous passage rates of ureteral stones less than 10 mm and serum C-reactive protein levels, white blood cell count and neutrophil percentages - Puntub, Atikhun; Lerdpraiwan, Weelak (Insight Urology, 2018)
Background and Objective : A ureteral obstruction that caused by ureteral stone results in inflammatory changes in the inner layer of ureter and prevents the spontaneous passage of the ureteral stone. The objective of this study is to determine the association between spontaneous passage rates of ureteral stones less than 10 mm and serum C-reactive protein levels, white blood cell count and neutrophil percentages. Materials and Methods : A prospective study was performed in 139 patients who were diagnosed with ureteral stones less than 10 mm in size from March 2016 – January 2017 at Phramongkutklao Hospital. Serum C-reactive protein, white blood cell count and neutrophil percentages were investigated before started medical expulsive therapy. All patients were followed at 4 weeks for spontaneous stone passage. The relationship between these factors and spontaneous stone passage were then examined. Results : The spontaneous ureteral stone passage rates of the normal serum C-reactive protein level group (0-5 mg/dL) and the high serum c-reactive protein level group were 67% (59/88) and 47.1% (24/51), respectively (p=0.021). The passage rates of ureteral stones in the normal white blood cell count group and the high white blood cell count group were 54.6% (65/109) and 60% (18/30), respectively (p=0.971). The passage rates of ureteral stones in the group with a normal neutrophil percentage and in the group with a higher neutrophil percentage were 58.6% (65/111) and 64.3% (18/28), respectively (p=0.581). On multivariate analysis, normal serum C-reactive protein level (OR=3.27, p=0.008), decreased age (OR=0.97, p=0.019), smaller size of stones (OR=0.61, p<0.001) and distal ureteral stones (OR=2.36, p=0.048) were associated with spontaneous ureteral stone passage. Conclusion : Serum C-reactive protein level has potential role to predict spontaneous stone passage in patients with ureteral stones less than 10 mm.